LOCAL WISDOM IN PINTO ACEH: A SEMIOTIC APPROACH - Khairun Nisyak; M. Manugeren; Purwarno Purwarno (AICLL: ANNUAL INTERNATIONAL CONFERENCE ON LANGUAGE AND LITERATURE, 2020)
This study aimed to investigate the cultural symbols and determine the local wisdom of Pinto Acehdescendants in Peunayong, Banda Aceh, Indonesia. In addition, the object of Pinto Aceh Motif and its local wisdom might not be forgotten and should be considered to enrich the horizon of knowledge. This study is descriptive qualitative and its empirical data was obtained from Simpang Lima Monument in Peunayong, Banda Aceh, Indonesia. This study was held in November 2019 up to December 2019 and the comprehensive data was gathered from informants who explained the meanings and values of cultural symbols, interpreted the hidden meanings, and determined the social relationships associated with the existing cultural symbols. The samples were selected from those who were knowledgeable in Pinto Aceh.One of the motives of the musical arrangement in the form of nature is Pinto Aceh motif. There are three local wisdoms that are based on Pinto Aceh's meaning, i.e. social integration, adherence to rules, and unity. Motif Pucok Paku 2 means Social Integration, Straight line motive means adherence to rules, and Curved line Motif means unity.The whole points of local wisdom in Pinto Aceh Motifs are highly needed to maintain the balance of life not only for the Aceh people but also for all the people respectively interconnected in the society, in which people should have a responsibility towards their surroundings. There are three local wisdom that is based on Pinto Aceh's meaning: social integration, adherence to rules, and unity.